Vaccination Status of Children Hospitalized for Measles: Parental Vaccination Refusal and Related Factors - Mürşide Zengin; Emriye Hilal Yayan; Mehmet Emin Düken (Galenos Yayinevi, 2022)
Aim:This study investigated the vaccination status of those children who received inpatient treatment due to measles and explored the beliefs and practices of their parents related to the refusal of childhood vaccines.Materials and Methods:This study was a descriptive research performed at a training and research hospital in eastern Turkey. The study data were collected from the parents of children with measles who were receiving inpatient treatment. In this study, the introductory information form and the State-Trait Anxiety Inventory were used.Results:The results revealed that 61.8% of those children with measles had not been vaccinated against measles. Factors that played a role in the parents' vaccine refusal included family elders' unwillingness, negative media reports, the side effects of vaccines, and negative attitudes towards health care workers. Parents with poor socio-economic status, low educational status, and extended family types were found to have significantly higher rates of vaccine refusal. The parents had an average state anxiety score of 60.15±5.73 and an average trait anxiety score of 50.21±3.33.Conclusion:Many factors were found to influence the causes of parents not having their children vaccinated. Community-based training is needed to address the parents' misconceptions, concerns, and lack of knowledge about vaccinations. Renewing policies on vaccinations, establishing standards, and imposing legal sanctions can be effective in reducing vaccine refusal rates.